Developing a framework to optimize teaching and learning in computing education: a study in technical institutes and polytechnics in New Zealand - Gunawardena, Kamani (Curtin University, 2013)
This study investigated students’ perceptions of their actual and preferred learning environments and their attitudes towards learning computer courses in New Zealand’s Polytechnics and Institutes of Technology. A mixed methodology was used to collect data. The relevant literature and the results of the data analysis aimed at answering three research questions and, further constructing a teaching framework to optimise teaching and learning computer courses. This study is expected to benefit the nominated education sector and future researchers.